PENGARUH CITRA MEREK DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG BERBASIS ANDROID DI KOTA BOGOR - Junaedi Junaedi; Titiek Tjahja Andari (Fakultas Ekonomi Universitas Djuanda, 2015)
This study aims to determine the effect of brand image and product attributes on purchasing decisions based Samsung android smartphone in Bogor. The sample in this study are based Samsung android smartphone users in Bogor with a sample of 100 respondents. The technique of multiple regression analysis, multiple correlation analysis, analysis of determination coefficient and hypothesis test using simultaneous F test and t test partially. Results showed that simultaneous brand image and product attributes affect the purchasing decisions in the city of Bogor. Partially, brand image and product attributes affect the purchasing decisions in the city of Bogor. The predictive capacity of these variables to-two on purchasing decisions by 53.5%. As it is shown the amount of R square of 53.5%, while the remaining 46.5% is influenced by other factors not included in this study.Keywords: Brand image, product attributes and Purchase Decision